PERKEMBANGAN PONDOK PESANTREN MODERN LIGA DAKWAH SUMATERA BARAT LUBUK MINTURUN KECAMATAN KOTO TANGAH PADANG TAHUN 1996 â 2013 - Yuliani, Silka - (Pendidikan Sejarah, 2014)
This research describes about the development of Pondok Pesantren Liga Dakwah Lubuk Minturun in 1996-2013 years. The background of the problem explains about the history, condition, the development, and the factors that influence the development of Pondok Pesantren Liga Dakwah. Exspreses about Pondok Pesantren Liga Dakwah in 1996-2013 but, in specifically, it describes Pondok Pesantren Liga Dakwah in 1996-2013 years. Then, the method of this research used the history method which the procedures include heuristic, it is to collect the data, then the critic of source, it is to do testing to the data which have been collected. after that interpretation. it is to comprehend the meaning and information which have been collected. The last, historiography it is the writing of article or thesis. The result of the research describes that Pondok Pesantren Liga Dakwah Lubuk Minturun built in 1996-2013 years. This Islamic school has the purpose to develop moslemâs behavior. as the Moslem, the people must be obedient an loyal to Allah S. W. T. in 1996, Pondok Pesantren Liga Dakwah built the education of senior high school students of Liga Dakwah. In 1996/1997 had 14 students then, in 1997/1998 had 6 students, 1998/1999 had 14 students, 1999/2000 had 12 students, 2001/2002 had 17 students. In every years, this school always increase the total of the students. Thus, it can be concluded that the development of Pondok Pesantren Liga Dakwah influence of the inspiration of Mr. H Yunizar to build Pondok Pesantren which consists of SMP and SMA in Pondok Pesantren. It also influence of the participation of board of education, the citizen and the bead master of Pondok Pesantren Liga Dakwah.